ISLAMISASI ILMU DAN IMPLIKASINYA TERHADAP KEBIJAKAN EKONOMI ISLAM DI ERA GLOBALISASI - Shafwa, Aqila Judya; Muhalimmy, Heru; Kamal, Kahila; Anggreini, Bunga; Adha, Azmi Airil (Media Riset Bisnis Ekonomi Sains dan Terapan, 2025)
This study examines the influence of the concept of Islamization of knowledge on the paradigm and formulation of Islamic economic policy in an era of globalization dominated by secular capitalist neoliberalism. The main issue raised is the research gap in the form of limited practical application of the Islamization of science which has so far been more epistemological and institutional in nature to the formulation of trade, fiscal, and monetary policies based on the principles of tawhid, maqasid sharia, and the values of justice and balance. The objectives of this research are to analyze how the ideas of Islamization of knowledge from figures such as al-Attas and al-Faruqi influence the framework of Islamic economic policy, identify its implications for contemporary policy, and formulate a strategic model to overcome implementation challenges amid global dynamics. The research uses a qualitative approach through library research with thematic content analysis of primary sources (the Qur'an, Hadith, works of Islamic thinkers) and secondary sources (journals and current literature). The results show that the Islamization of knowledge produces a holistic alternative economic paradigm, integrating tauhid, khilafah, rububiyyah, and tazkiyah into monetary (profit-loss sharing), fiscal (ZISWAF), and real sector policies, and offers a strategic model based on maqasid sharia to achieve economic justice, inclusiveness, and sustainability in the era of globalization.Keywords : Economic Globalization, Islamic Economics, Islamization of Science, Economic Policy, Maqasid Sharia